Models for assessimg general horizontal swimming abilities of junior water polo players according to playing position - Özkol, Z.; Dopsaj, M.; Thanopoulos, V.; Bratusa, Z. (Biomechanics and Medicine in Swimming XI, 2010)
The aim of this study was to identify general level of horizontal swimabilities of junior water polo players according to playing position. The subjects were 71 players, members of national junior teams. The players were divided in three main playing position groups; peripherals (P), center defenders (CD) and center players (C). The following six swimming tests were performed, crawl; 15m, 25m, 50m, 200m, 25m crawl with head up and 25m crawl with ball. The results of these tests were analyzed using a confirmative model of factor analysis for the determination of the factor scores and mathematical multidimensional procedures were determined for creating models. There were no statistical differences (p>0.05) between general level of basic horizontal swim abilities according to position.